Social-demographic characteristics of Induced abortion patients in a tertiary care hospital of Dhaka Bangladesh - Akhter, Kulsum; Nahar, Shamsun; Khan, Samjida (The Insight, 2022)
Introduction: Abortion is a major social and public health concern. Complications from unsafe abortions are one of the primary causes of maternal death in Bangladesh. It's a major health issue. According to the World Health Organization, 14 percent of maternal fatalities are preventable which occur every year in South Asian nations, including Bangladesh, are caused by abortion. However, there is a lack of up-to-date and reliable information on induced abortion distribution and its determinant factors in the country. This study was intended to assess induced abortion and associated factors in a tertiary care center in Bangladesh Aim of the study: The aim of the study was to observe the social and demographical characteristics of induced abortion patients admitted to a tertiary care hospital in Bangladesh. Methods: This prospective observational study was conducted at the Department of Obstetrics and Gynaecology, Dhaka Medical College Hospital, Bangladesh. The study duration was 6 months, from May 2007 to October 2007. A total of 80 cases were randomly selected from all induced abortion cases admitted in different maternity units of Dhaka Medical College Hospital (DMCH). Result: 50% of the participants were between the age of 21-30 years, all except 12.5% of the participants were multipara, a majority (46.25%) had 6-12 weeks of pregnancy before termination. The most common clinical presentation was amenorrhea and pervaginal bleeding, followed by pain in the abdomen. The majority of the participants (58.75%) were housewives, and 93.75% were from a low socio-economic class. 85% were from urban areas, and 60% were illiterate. Conclusion: The prevalence of induced abortion was extremely high among women of low social class with little to no education, and most of them were housewives or day laborers. Early abortion resulted in fewer complications, whereas late abortion resulted in a higher risk of complications. Amenorrhea, pervaginal bleeding, and abdominal pain were the most common complications among the admitted participants.